Islamic Republic of Mauritania : Economic Development Documents. (IMF Staff Country Reports; Country Report, 2018)
This Economic Development Document summarizes Mauritania's Strategy for Accelerated Growth and Shared Prosperity (SCAPP) for 2016-30. The first five-year phase of the SCAPP will complete projects under way and lay the foundations for a new, politically more peaceful Mauritania, with infrastructure put in place to support growth and encourage development of the country's natural resources. Steps will be taken to complete the reforms needed to improve the business climate and promote the private sector. In the second five-year period, the economy will be more diversified and competitive, with the real rate of growth averaging at about 10 percent a year. The third five-year phase will consolidate Mauritania's 'new look' and the economic growth will exceed 12 percent a year.